2022
DOI: 10.1071/cp21342
|View full text |Cite
|
Sign up to set email alerts
|

Silicon and zinc nanoparticles-enriched miscanthus biochar enhanced seed germination, antioxidant defense system, and nutrient status of radish under NaCl stress

Abstract: Context Soil salinity mitigation with nanoparticles enriched biochar (Bc) can be a better strategy to resolve the uprising threat against food security. Aim The present study was designed to prepare silicon nanoparticles enriched biochar (Si-En-Bc) and zinc nanoparticles enriched biochar (Zn-En-Bc), which may not only reduced the toxic effects of NaCl stress on initial growth of radish crop but also improved its physiology and defensive mechanism. Method Seeds were germinated in pots with six tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 90 publications
0
15
0
Order By: Relevance
“…Not only pure BC but BC combined with various nanoparticles also promotes seed germination. Taqdees et al (2022) reported that BC enriched with silicon nanoparticles (Si-BC) and zinc nanoparticles (Zn-BC) enhanced the seed germination of salt-stressed radish. Thus, BC can play a vital role in the seed germination of different horticultural crops under normal and stressed conditions.…”
Section: Biochar Improves Seed Germination Of Horticultural Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Not only pure BC but BC combined with various nanoparticles also promotes seed germination. Taqdees et al (2022) reported that BC enriched with silicon nanoparticles (Si-BC) and zinc nanoparticles (Zn-BC) enhanced the seed germination of salt-stressed radish. Thus, BC can play a vital role in the seed germination of different horticultural crops under normal and stressed conditions.…”
Section: Biochar Improves Seed Germination Of Horticultural Cropsmentioning
confidence: 99%
“…Biochar has a multifunctional role, including GHG sequestration, improving soil properties, seed germination, crop yield and quality of horticulture produce, and increasing crop tolerance to abiotic and biotic stresses ( Kochanek et al., 2016 ; Almaroai and Eissa, 2020 ; Zulfiqar et al., 2021a ; Zulfiqar et al., 2021b ; Ibrahim et al., 2022 ; Ji et al., 2022 ; Taqdees et al., 2022 ) ( Figure 2 ). This review summarizes current progress on using BC to improve soil and substrate properties, seed germination, root growth, water and nutrient absorption, photosynthesis, crop yield, and tolerance to plant pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Modification of biochar by chemical reagents increases the number of functional groups on its surface area, which ultimately improves the adsorption capacity of this organic material (Li et al, 2020;Liu et al, 2022). In a recent study, Taqdees et al (2022) showed that biochar modification with zinc particles improved radish growth under salt stress via decreasing sodium uptake by plants and enriching plant cells with zinc cations. In another study, Wen et al (2021) reported that soil treatment by iron-modified biochar increases the cadmium sorption capacity of biochar, plant growth, and soil health in contaminated soils.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been observed that biochar doped with magnetic Fe resulted in a larger percentage of C functional groups for nutrient and metal adsorption [47]. In our previous studies, Fe, Zn and Si enrichment on the BC surface enhanced the plant growth and its physiology even at a lower rate of application (0.5 or 1%) under different abiotic stresses [1,32,48]. Hence, a huge amount of exchequer can be saved by using the elemental-enriched BC on a commercial scale in degraded soils.…”
Section: Economics Of Bc and Its Limitationsmentioning
confidence: 92%